Ticks and Tick-Borne Pathogens of the Caribbean: Current Understanding and Future Directions for More Comprehensive Surveillance - Gondard, Mathilde; Cabezas-Cruz, Alejandro; Charles, Roxanne A.; Vayssier-Taussat, Muriel; Albina, Emmanuel; Moutailler, Sara (Frontiers in Cellular and Infection Microbiology, 2017)
Ticks are obligate hematophagous arthropods of significant importance to human and veterinary medicine. They transmit a vast array of pathogens, including bacteria, viruses, protozoa, and helminths. Most epidemiological data on ticks and tick-borne pathogens (TBPs) in the West Indies are limited to common livestock pathogens such as Ehrlichia ruminantium, Babesia spp. (i.e., B. bovis and B. bigemina), and Anaplasma marginale, and less information is available on companion animal pathogens. Of note, human tick-borne diseases (TBDs) remain almost completely uncharacterized in the West Indies. Information on TBP presence in wildlife is also missing. Herein, we provide a comprehensive review of the ticks and TBPs affecting human and animal health in the Caribbean, and introduce the challenges associated with understanding TBD epidemiology and implementing successful TBD management in this region. In particular, we stress the need for innovative and versatile surveillance tools using high-throughput pathogen detection (e.g., high-throughput real-time microfluidic PCR). The use of such tools in large epidemiological surveys will likely improve TBD prevention and control programs in the Caribbean.